THE VICE-CHANCELLOR CONGRATULATES AND EXTENDS APPRECIATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 11 May 2016 - The USM Vice-Chancellor Professor Dato' Dr. Omar Osman congratulated Professor Dr. Abdul Rahman Mohamed who has been appointed as the Deputy Vice-Chancellor (Industry and Community Network) and Professor Dato' Dr. Muhamad Jantan in resuming his service as the Deputy Vice-Chancellor (Research and Innovation).